PENGARUH LIMBAH PLASTIK POLYTHYLENE SEBAGAI ASPAL POLIMER DITINJAU DARI UJI SIFAT MARSHALL - Diana Suita; Dr. Rahmat Dirgantara (Universitas Harapan Medan, 2020)
In 1999, the Department of Regional Development issued a specification regarding the Guidelines of planning mixed hot asphalt with absolute density apporach (Pedoman Perencanaan Campuran beraspal Panas dengan Pendekatan Kepadatan Mutlak). One of the specifications issued is Asphalt Concrete – Wearing Course (AC – WC) as the second layers in tiers of different types of asphalt concrete is the topmost layer in the roughness supple. Generally, asphalt is used as a binder, in a mix of this AC – WC uses LLDPE 5% and 7% as a substitute of most asphalt, in order to increase the value of its stability, as well as one of the concrete steps as handling reductiong waste that is difficult to unravel with the increase in the value of the function. Stages of asphalt mixture with LLDPE as a substitute of most asphalt include testing asphalt, Fine Aggregate, Coarse Aggregate and Filler Testing in order to find out its characteristic against Marshall Test. The highest percentage in the early immersion is owned by a mixture with pure sample levels, then followed by the addition of 5% and 7% of LLDPE in lieu of most asphalt. The results of testing gravity on the aggregate of split stone is 2.576gr/cc. Levels of asphalt plan which will be used for pure sample is 6.25% of total mixture, followed by 6.25 with a mixture of 5% LLDPE and 6.25 mixed with 7% LLDPE. The results are 5% flow is 3,70, 7% LLDPE is 3.70%, the stability of 5% and 7% LLDPE are 924 kg/cm2 and 735kg/cm2 , and Marshall Quotient 5% and 7% of the linear low density poly ehylene is 255.00 kg and 200,00 kg.